Implementation of Library Digitalization System as an Effort Improving Educational Literacy in South Sulawesi - Syahdan Syahdan; Ismaya Maya Maya; Andi Ahmad Chabir Galib; Madinatul Munawwarah Ridwan; Fitra Udin; Rahma Rahma; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2024)
Library digitization is key to enhancing accessibility and the utilization of information in order to improve educational literacy in the digital era. South Sulawesi, as part of Indonesia’s rapidly developing region, needs to strengthen its information infrastructure, such as digital libraries, to address users' behavior towards technological advancements. The objective of this research is to analyze the implementation of the library digitization system in South Sulawesi by evaluating implementation strategies, identifying success factors and challenges, and understanding its impact on library services and public access to information. This research employs a mixed methods approach, combining quantitative and qualitative data analysis in parallel. Quantitatively, surveys (both offline and online) were conducted to collect data on implementation strategies, success factors, and barriers to library digitization. Qualitatively, in-depth interviews and document analysis were used to explore the impact of library digitization on services and public access to information. The results show that the level of library digitization implementation in South Sulawesi remains low. Existing digitization strategies vary but are generally hindered by limited infrastructure and human resources. Success factors include government support and collaboration with other institutions, while the main challenges involve insufficient funding, resistance to change, and low digital literacy among the population. The positive impacts of digitization include improved access to information and better quality library services, although there are still challenges in maintaining the systems. Key recommendations include improving infrastructure, staff training, and increasing public digital literacy.